KEMAMPUAN RASIO LIKUIDITAS DAN SOLVABILITAS DALAM MEMPREDIKSI LABA PERUSAHAAN PERUSAHAAN: STUDI EMPIRIS PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yusra, Irdha (Jurnal Benefita, 2016)
This research as a purpose to know what influence of liquidity and solvency ratio toward profitability ratio. Sample from this research is five enterprise in Indonesian Stock Exchange period 2007-2014. The data analysis technique used multiple linear regression analysis using Eviews 6. From the results of tests performed showed that liquidity statistically not significant affect profitability, as indicated by the probability of > 0,05 is 0,2761. Be different with solvency who were statistically significantly profitability, which is indicated by the probability of < 0,05 is 0,0460.